2002
DOI: 10.1097/00004647-200212000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Widespread and Long-Lasting Alterations in GABAA-Receptor Subtypes After Focal Cortical Infarcts in Rats: Mediation by NMDA-Dependent Processes

Abstract: Impairment of inhibitory neurotransmission has been reported to occur in widespread, structurally intact brain regions after focal ischemic stroke. These long-lasting alterations contribute to the functional deficit and influence long-term recovery. Inhibitory neurotransmission is primarily mediated by gamma-aminobutyric acid (GABA)A receptors assembled of five subunits that allow a variety of adaptive changes. In this study, the regional distribution of five major GABA(A)-receptor subunits (alpha1, alpha2, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 53 publications
5
71
0
Order By: Relevance
“…In this study, α 1 subunit mRNA transcript and protein expression did not correspond, possibly due to a translation block and/or a post-translational modification reported by others (NeumannHaefelin et al, 1999). Comparison of the present results of α 1 subunit mRNA and protein expression with those of other studies (Neumann-Haefelin et al, 1998, 1999Redecker et al, 2002) revealed several differences. α 1 mRNA levels were shown to increase threefold ipsilaterally at 7 days following photothrombosis of the primary somatosensory cortex (Neumann-Haefelin et al, 1999), whereas a moderate decrease of corresponding protein was observed (Neumann-Haefelin et al, 1998).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In this study, α 1 subunit mRNA transcript and protein expression did not correspond, possibly due to a translation block and/or a post-translational modification reported by others (NeumannHaefelin et al, 1999). Comparison of the present results of α 1 subunit mRNA and protein expression with those of other studies (Neumann-Haefelin et al, 1998, 1999Redecker et al, 2002) revealed several differences. α 1 mRNA levels were shown to increase threefold ipsilaterally at 7 days following photothrombosis of the primary somatosensory cortex (Neumann-Haefelin et al, 1999), whereas a moderate decrease of corresponding protein was observed (Neumann-Haefelin et al, 1998).…”
Section: Discussionsupporting
confidence: 50%
“…Although immunohistochemical techniques can demonstrate distinct laminar and regional distributions of GABA A R α 1 protein in intact and injured cortex (Fritschy and Mohler, 1995;Redecker et al, 2002), α 1 protein expression levels in this study were assessed from commingled tissue punches taken from different cortical areas; good correlation has been demonstrated between Western immunoblotting and immunohistochemical techniques applied for the analysis of GABA A R subunit proteins (Harris et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the severity of the primary insult may correlate not only with the extent of the secondary lesion but may also explain reversibility. 117 Interestingly, Witte and co-workers 135 elegantly described widespread and long-lasting dysregulation of the GABAergig system after focal cortical infarcts in regions with and without delayed exofocal cell death.…”
Section: Snl In Remote Areas After Focal Ischemia Neuropathologymentioning
confidence: 99%
“…Numerous studies have shown that PT induces periinfarct depolarization closely related to CSD (Dietrich et al, 1994;Jander et al, 2000) and other neurophysiologic alterations in the ipsilateral hemisphere such as increased spontaneous activity of neurons (Schiene et al, 1996). Remote molecular alterations encompass upregulation of proinflammatory cytokines and growth factors (Jander et al, 2000;Kleinschnitz et al, 2004), and rearrangement of neurotransmitter receptors (Redecker et al, 2002). Magnetic resonance imaging studies using the contrast agent gadolinium diethylenetriamine-pentaacetic acid (Gd-DTPA) as the conventional in vivo marker for the BBB showed early and long-lasting breakdown of the BBB within the PT lesion (Lee et al, 1996;Schroeter et al, 2001;Kleinschnitz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%